Search for Dark Photons from Supersymmetric Hidden Valleys - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Ochando, C.; et al. (Amer Physical Soc, 2009)
We search for a new light gauge boson, a dark photon, with the D0 experiment. In the model we consider, supersymmetric partners are pair produced and cascade to the lightest neutralinos that can decay into the hidden sector state plus either a photon or a dark photon. The dark photon decays through its mixing with a photon into fermion pairs. We therefore investigate a previously unexplored final state that contains a photon, two spatially close leptons, and large missing transverse energy. We do not observe any evidence for dark photons and set a limit on their production.